TWO-STROKE ENGINE BEHAVIOR (SMALL CHAINSAW) OPERATING WITH NON-COMMERCIAL FUEL BLENDS AND DIVERSE LUBRICATION - L. da Silva, R.; Vieira, M. M.; de Brito Jr, S. X. (Revista de Engenharia Térmica, 2015)
The paper presents results for experimental tests in a two-stroke internal combustions engine operating on commercial fuel (gasoline and ethanol blends), with different proportions in mineral oil for lubrication purposes. Appropriate instrumentation was used to carry out the measurement of the quantities of interest, namely fuel consumption (g/s), angular velocity (rpm) and emissions (CO2 and NOx). The methodology was based on regulations from INMETRO (motor vehicles energy conversion efficiency) and ABNT (testing of internal combustion engines). Results obtained are analyzed and discussed for the fuel consumption versus angular velocity (g/s x rpm) for each combination fuel blend and lubricating oil (quantities). Main findings are that fuel consumption increases non linearly as angular velocity increases and as lubrication lowers, while emissions decreases as angular velocity increases. Lowest fuel consumption and emissions occurred, respectively, for A25/L1:25 and A25/L1:50 (commercial fuel and standard lubrication).